Efficacy and safety of idebenone tablets in patients with post-stroke cognitive impairment: a real-world study - Shao, Yanqi; Zhao, Xinyu; Xie, Zunchun; Xie, You; Guo, Shunyuan (Frontiers in Neurology, 2025)
ObjectiveTo evaluate the efficacy, safety, and adherence of idebenone tablets in improving cognitive function among patients with post-stroke cognitive impairment in a real-world setting.MethodsThis single-arm, multicenter, real-world observational study enrolled 3,755 patients with post-stroke cognitive impairment from 342 hospitals across China between January 2020 and December 2024. Patients received idebenone (30 mg three times daily) for 3 months. Cognitive function was assessed using MoCA and MMSE at baseline and months 1, 2, and 3. Treatment effectiveness was categorized as markedly effective (≥80% improvement), effective (30–79% improvement), or ineffective (<30% improvement).ResultsOf the 3,755 patients (mean age 60.7 ± 10.4 years; 58.5% male), 61.8% had hypertension and 48.4% had ischemic stroke. The total effectiveness rate increased progressively from 10.9–13.0% at month 1 to 37.4–38.2% at month 3 for both MoCA and MMSE scores (p < 0.001). MoCA scores improved from 14.6 ± 5.1 at baseline to 17.6 ± 6.2 at month 3, while MMSE scores increased from 14.2 ± 4.6 to 17.5 ± 6.2. High medication adherence (≥80%) was achieved by 96.9% of patients. Only mild adverse events were reported in less than 2% of patients, with no severe adverse events documented.ConclusionThis real-world study suggests that three-month idebenone therapy provides meaningful improvements in cognitive function among patients with post-stroke cognitive impairment, with excellent safety and adherence profiles. However, the observational, single-arm design without a control group means that observed improvements cannot be definitively attributed to the intervention alone. Further randomized controlled trials are warranted to confirm these findings and optimize treatment protocols.